A Solvent-Free Surface Suspension Melt Technique for Making Biodegradable PCL Membrane Scaffolds for Tissue Engineering Applications - Ratima Suntornnond; Jia An; Ajay Tijore; Kah Fai Leong; Chee Kai Chua; Lay Poh Tan (Molecules, 2016)
In tissue engineering, there is limited availability of a simple, fast and solvent-free process for fabricating micro-porous thin membrane scaffolds. This paper presents the first report of a novel surface suspension melt technique to fabricate a micro-porous thin membrane scaffolds without using any organic solvent. Briefly, a layer of polycaprolactone (PCL) particles is directly spread on top of water in the form of a suspension. After that, with the use of heat, the powder layer is transformed into a melted layer, and following cooling, a thin membrane is obtained. Two different sizes of PCL powder particles (100 µm and 500 µm) are used. Results show that membranes made from 100 µm powders have lower thickness, smaller pore size, smoother surface, higher value of stiffness but lower ultimate tensile load compared to membranes made from 500 µm powder. C2C12 cell culture results indicate that the membrane supports cell growth and differentiation. Thus, this novel membrane generation method holds great promise for tissue engineering.